Validation and Sensitivity Analysis of a 1‐D Lake Model Across Global Lakes. Issue 4 (17th February 2021) - Guo, Mingyang; Zhuang, Qianlai; Yao, Huaxia; Golub, Malgorzata; Leung, L. Ruby; Pierson, Don; Tan, Zeli
Abstract: Lakes have important influence on weather and climate from local to global scales. However, their prediction using numerical models is notoriously difficult because lakes are highly heterogeneous across the globe, but observations are sparse. Here, we assessed the performance of a 1‐D lake model in simulating the thermal structures of 58 lakes with diverse morphometric and geographic characteristics by following the phase 2a local lake protocol of the Intersectoral Impact Model Intercomparison Project (ISIMIP2a). After calibration, the root‐mean‐square errors (RMSE) were below 2°C for 70% and 75% of the lakes for epilimnion and full‐profile temperature simulations, with an average of 1.71°C and 1.43°C, respectively. The model performance mainly depended on lake shape rather than location, supporting the possibility of grouping model parameters by lake shape for global applications. Furthermore, through machine‐learning based parameter sensitivity tests, we identified turbulent heat fluxes, wind‐driven mixing, and water transparency as the major processes controlling lake thermal and mixing regimes. Snow density was also important for modeling the ice phenology of high‐latitude lakes. The relative influence of the key processes and the corresponding parameters mainly depended on lake latitude and depth. Turbulent heat fluxes showed a decreasing importance in affecting epilimnion temperature with increasing latitude. Wind‐driven mixing was less influential to lake stratification for deeper lakes while the impact of light extinction, on the contrary, showed a positive correlation with lake depth. Our findings may guide improvements in 1‐D lake model parameterizations to achieve higher fidelity in simulating global lake thermal dynamics. Key Points: By testing against a highly diverse lake observation data set, Arctic Lake Biogeochemistry Model is shown to be capable of simulating global lake thermal dynamics Turbulent heat fluxes, wind‐driven mixing, water clarity, and snow density are the main uncertainty sources for modeled lake thermal regimes The relative importance of the key processes depends on lake latitude and depth